Tourism Potential of The Dieng Culture Festival in Increasing Community Income and Development Strategy - Rochmat Aldy Purnomo; Aulia Hapsari Juwita; Noor Ismawati Jaafar; Oksana Malynka; Sri Hartono; Hadi Sasana (EKO-REGIONAL, 2023)
The purpose of this study is to analyze the potential of the Dieng Culture Festival (DCF) tourism performance in increasing the community income around Dieng and develop the strategy for the Dieng Culture Festival. To collect the data, the techniques of observation, interviews, and literature study were used. The selected research respondents included the Tourism Awareness Group Chairperson and street vendors around the DCF tourist complex. 40 street vendors were selected as samples using a stratified random sampling method. This research was done during the 2022 Dieng Culture Festival, using the SWOT and QSP Matrix methods. The results showed that the development strategy for the Dieng tourism program was the WT strategy aimed at minimizing weaknesses and avoiding external threats. In addition, the DCF increased the number of tourists enjoying the Dieng tourist complex and the income of street vendors.